Trephine Craniotomy versus Burr Hole Drainage for Chronic Subdural Hematoma—An Institutional Analysis of 156 Patients - Vemula, Ramesh Chandra; Prasad, B. C.M.; Koyalmantham, Venkat; Kumar, Kunal (Indian Journal of Neurotrauma, 2020)
Introduction Some neurosurgeons believe that doing a trephine craniotomy (TC) decreases the chance of recurrence in chronic subdural hematoma (cSDH). But this is not supported by any evidence.Methods A retrospective analysis of patients who were operated for cSDH from 2014 to 2019 at our institute was done. Factors causing recurrence were studied.Results A total of 156 patients were operated in the given period, among which 88 underwent TC and 68 patients underwent burr hole drainage (BHD) for evacuation of cSDH. All patients underwent two trephines or two burr holes placed according to the maximum thickness of the hematoma. Rate of recurrence in trephine group was 12.5% and in burr-hole group was 11.76% and was not statistically significant. Significant factors for recurrence included nontraumatic cSDH, anticoagulant use, presence of membranes, preoperative computed tomography (CT) showing iso- or mixed-density subdural collection and SDH volume > 60 mL. There was selection bias for the procedure. Patients with subdural membranes were preferentially taken for TC as the percentage of subdural membrane found intraoperatively was significantly greater in trephine group (51.1%) than burr-hole group (17.6%) (p value < 0.001).When all the patients who showed membranes in CT scan were excluded, there was no statistical difference in the base line characteristics of both the groups. After excluding the patients with membranes in preoperative CT scan, there was no significant difference in recurrence rate between the two groups.In TC group with membranes, 8 out of 45 had recurrence, whereas in burr-hole group with membranes, 8 out of 12 had recurrence. This difference was statistically significant. (p value < 0.001).Conclusion Surgical intervention in both modalities improves patient outcome with an overall recurrence rate of 12.17%. In the absence of any identifiable membranes in preoperative CT scan, BHD is the preferred surgical intervention. We prefer TC as first choice for patients with membranes in CT scan.
Keywords: burr hole drainage; chronic subdural hematoma (SDH); recurrence; risk factors; trephine craniotomy